3D printable photochromic molecular materials for reversible information storage - Wales, Dominic J.; Cao, Qun; Kastner, Katharina; Karjalainen, Erno; Newton, Graham N.; Sans, Victor (Wiley, 2018)
The formulation of advanced molecular materials with bespoke polymeric ionic liquid matrices that stabilize and solubilize hybrid organic-inorganic polyoxometalates and allow their processing by additive manufacturing, is effectively demonstrated. The unique photo and redox properties of nanostructured POMs are translated across the scales (from molecular design to functional materials) to yield macroscopic functional devices with reversible hotochromism. These properties open a range of potential applications including reversible information storage based on controled topological and temporal reduction/oxidation of pre-formed printed devices. This approach pushes the boundaries of 3D printing to the molecular limits, allowing us to couple the freedom of design enabled by 3D printing with the molecular tuneability of polymerizable ionic liquids and the photoactivity and orbital engineering possible with hybrid polyoxometalates.